Pregnancy in Infertile Patient after Intrauterine Adhesiolysis by Multitherapeutic Strategy: A Case Report and Mini-review - Hoang The Dinh; Nhan Trong Nguyen; An Nguyen Phuong Tran (Wolters Kluwer Medknow Publications, 2024)
Asherman's syndrome, characterized by intrauterine adhesions (IUAs), represents a significant challenge in the field of female infertility. Hysteroscopic adhesiolysis has emerged as the gold standard for both the diagnosis and treatment of Asherman's syndrome. Understanding the intricate relationship between Asherman's syndrome, uterine adhesiolysis, and infertility is crucial for guiding comprehensive and effective management strategies. The success of the treatment is contingent upon preventing adhesion recurrence, particularly in cases of severe IUAs. This is the first case, in which we employed a multifaceted preventive approach, utilizing hyaluronic gel, Foley balloon, hormonal therapy, and platelet-rich plasma, achieving successful pregnancy following embryo transfer despite the presence of severe IUAs. The patient, a 35-year-old female, underwent one cesarean section following in vitro fertilization and required dilation and curettage due to retained products of conception. The patient presented with oligohemorrhage, and the uterine lining was thin while using hormones for endometrial preparation. The diagnosis of severe IUAs was confirmed through ultrasound and hysteroscopic examination of the uterine cavity. The patient underwent hysteroscopic adhesiolysis with a preventive approach using a combination of methods. Subsequently, the patient underwent a second-look hysteroscopy to assess the uterine cavity and achieved successful embryo transfer. The patient carried the pregnancy to 38 weeks and underwent repeated cesarean section due to the vertex-vertex presentation of the twins.